Impact of Various Types Of Water Repellent Agent Towards Concrete Engineering Performance - Tang, Hou Jing (2021)
Concrete can be categorised into three types such as heavyweight, normalweight and lightweight. In this study, lightweight concrete was studied with the use of water repellent agent (WRA) due to the lightweight concrete have a more porous structure. Lightweight concrete is further classified into lightweight aggregate concrete (LAC), lightweight foamed concrete (LFC) and autoclaved aerated concrete. In this study, only the LAC and LFC were chosen to study with the incorporation of various WRA. Five types of WRA that used to study were calcium stearate (CS), zinc stearate (ZS), sodium oleate (SO), silane and siloxane. This study aims to apply these five types of WRA to investigate their impact on the LAC and LFC in terms of compressive strength and water absorption. Next objective of this study is to analyse the most effective WRA for respective LAC and LFC. The qualitative method had been adopted wherein an extensive review of research articles had been carried out. Keywords such as LAC and LFC with the use of WRA to search and filter. SWOT analysis was adopted to examine the most effective WRA for LAC and LFC. Results showed that these five types of WRA would reduce the compressive strength of LAC and LFC. Also, the water absorption of LAC and LFC would reduce with the incorporation of WRA. Results showed that ZS and CS were the optimal WRA for the respective LAC and LFC in terms of compressive strength and water absorption. Thus, ZS and CS can be widely used in the construction industry to produce water-resistant lightweight concrete.